Crescimento, produção e composição química do óleo essencial de Martianthus leucocephalus (Mart. ex Benth.) J. F. B. Pastore em condições de Feira de Santana, Bahia, Brasil - Azevedo, Bianca Oliveira de (2014)
Lamiaceae is a family of flowering plants of great importance due to its aromatic herbs with pharmaceutical properties. Endemic species from the semiarid region of Brazil, as Martianthus leucocaphalus (Mart. Ex Benth.) J. F. B. Pastore, produce essential oils of great phytochemical and economic potential, due to its proven antimicrobial and antifungal activities. This species is not yet commercially cropped, but it is already known that biotic and abiotic factors play an important role on the production of essential oils, making it difficult to to explore these compounds. In this sense, we aimed to evaluate the effect of climate in different months of the year in edaphoclimatic conditions of Feira de Santana, BA, on the growth, production and composition of essential oil from M. leucocaphalus. Experiments were performed on Horto Florestal Experimental Unit from Universidade Estadual de Feira de Santana. We monthly quantified growth, by foliar area parameters, using fresh and dried leaves, branches and inflorescences. In each period we evaluated content and chemical composition of essential oilds under a combination of Gas Chromatography techniques (CG), in order to quantify constituents and Gas Chromatography coupled to Mass Spectrometry (CG/EM) to identify these constituents. Climatic data were obtained over INMET. Obtained data were analyzed under SAS, using Spearman correlation among variables and descriptive statistics. A mean test was performed on SISVAR for comparison. Total dried mass (MST) and essential oil content (TO) were higher on months of great solar intensity and lower on months with abundant precipitation. Constituents varied considerably due to climatic factors, with major concentration of the majoritary compound on more humid months with a low solar irradiance.